2015
DOI: 10.1098/rsta.2015.0073
|View full text |Cite
|
Sign up to set email alerts
|

Green process for green materials: viable low-temperature lipase-catalysed synthesis of renewable telechelics in supercritical CO 2

Abstract: SummaryWe present a novel near ambient temperature approach to telechelic renewable polyesters by exploiting the unique properties of supercritical CO2 (scCO2). Bio-based commercially available monomers have been polymerised and functional telechelic materials with targeted molecular weight were prepared by end-capping the chains with molecules containing reactive moieties in a one-pot reaction. The use of scCO2 as a reaction medium facilitates the effective use of Candida Antarctica Lipase B (CaLB) as a catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Moreover, biobased telechelic polyesters were produced via N435-catalyzed polycondensation of azelaic acid and 1,6-HDO with different functional end-cappers in supercritical CO 2 [258]. The trueMn¯, dispersity and reaction yield of the resulting telechelic poly(hexamethylene azelate)s were around 1500–2400 g/mol, 1.73–2.18, and 78%–88%, respectively.…”
Section: Lipase-catalyzed Synthesis Of Sustainable Polyesters and mentioning
confidence: 99%
“…Moreover, biobased telechelic polyesters were produced via N435-catalyzed polycondensation of azelaic acid and 1,6-HDO with different functional end-cappers in supercritical CO 2 [258]. The trueMn¯, dispersity and reaction yield of the resulting telechelic poly(hexamethylene azelate)s were around 1500–2400 g/mol, 1.73–2.18, and 78%–88%, respectively.…”
Section: Lipase-catalyzed Synthesis Of Sustainable Polyesters and mentioning
confidence: 99%
“…Avoidance of branching is important because as branching increases, the number of pendant hydroxyl groups on the polymer chain is decreased, and this compromises water solubility. 36,37 Control experiments were also performed in scCO2 without CaLB and under the more traditional melt polymerisation conditions at 120°C with and without CaLB. Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…This interaction offers the opportunity that scCO2 could act as a processing aid in polymerisation, lowering viscosity and improving mass transfer of monomers to the catalyst or enzyme. 36,37 A series of polymerisations of succinic acid and glycerol were trialled using CaLB (25 wt.% wrt monomer including polymer support) to gauge the effect of temperature (40, 50 and 60 ºC) and molar ratio of the monomers (Table 1). ×100 by integrating the resonances corresponding to the Hb protons from the B0 and B1 structures, using 1 H-NMR and focussing on proton Hb (see Figure 1).…”
Section: Enzymatic Polycondensation Of Poly(glycerol Succinate) Under Supercritical Conditionsmentioning
confidence: 99%
“…In addition, the enzyme could be washed and re-used as has been previously demonstrated. 31,32 Potentiometric titrations showed that there are considerably more hydroxyl groups than carboxylic acid groups in the samples from the enzymatic and carbonate catalysed polymerizations (Table 1). This excess of hydroxyl groups suggests that ring closure and branching, which are a consequence of the reaction of the secondary alcohol groups of sorbitol, have been minimised.…”
Section: Polymer Chemistrymentioning
confidence: 99%